2020
DOI: 10.1177/0963689720925059
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: LncRNA FEZF1-AS1 Modulates Cancer Stem Cell Properties of Human Gastric Cancer Through miR-363-3p/HMGA2

Abstract: Gastric cancer (GC) is a leading cause of cancer-related death with poor prognosis. Growing evidence has shown that long noncoding ribonucleic acid (lncRNA) FEZ family zinc finger 1 antisense RNA 1(FEZF1-AS1), an “oncogene,” regulates tumor progression and supports cancer stem cell. However, the tumorigenic mechanism of FEZF1-AS1 on gastric cancer stem cell (GCSC) is yet to be investigated. Here, we discovered that FEZF1-AS1 was upregulated in GC tissues and cell lines. Knockdown of FEZF1-AS1 inhibite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 56 publications
1
14
0
Order By: Relevance
“…The luciferase assay verified that miR ‐ 363 ‐ 3p could bind to the 3′‐UTR of CELF2 . It has been reported that miR ‐ 363 ‐ 3p is involved in multiple processes during tumour development 27‐29 . We performed a series of experiments to confirm biological functions of miR ‐ 363 ‐ 3p .…”
Section: Discussionmentioning
confidence: 98%
“…The luciferase assay verified that miR ‐ 363 ‐ 3p could bind to the 3′‐UTR of CELF2 . It has been reported that miR ‐ 363 ‐ 3p is involved in multiple processes during tumour development 27‐29 . We performed a series of experiments to confirm biological functions of miR ‐ 363 ‐ 3p .…”
Section: Discussionmentioning
confidence: 98%
“…Silencing of lncRNA HEIH inhibits liver cancer cell growth and metastasis through miR-199a-3p/mTOR axis [ 29 ]. Hui et al have found that FEZF1-AS1 modulates cancer stem cell properties through miR-363-3p/HMGA2 axis in GC [ 30 ]. LncRNA DCST1-AS1 has proved that it could regulate cell proliferation and apoptosis in GC by targeting miR-605-3p [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…GC-derived exosomes carrying miR-107 are able to promote MDSC expansion and activation via targeting DICER1 and PTEN, therefore suppressing tumor growth and augmenting immunotherapy efficacy (Ren et al, 2019). Recently, Zhang et al revealed that EVs loaded with miR-130b-3p mediate communication between GC cells and M2 macrophages in the tumor microenvironment by modulating MLL3 and GRHL2 (Zhang Y. et al, 2020). According to data from the TCGA database, lncRNA RP11-323N12.5 is identified as the most significantly upregulated lncRNA in GC.…”
Section: Tumor Immune Escapementioning
confidence: 99%